Penerapan PP 46 Tahun 2013 Dalam Analisis CVP Untuk Membantu Perencanaan dan Pengambilan Keputusan UMKM - Norman Duma Sitinjak (University of Merdeka Malang, 2017)
To increase state revenue and help SMEs in the calculation of the tax, the Government of Indonesia issued PP 46 2013. That regulation tax is for businesses with gross earnings in a tax year less than Rp. 4.8 billion. It will be charged by 1% tax rate on gross income. Tax will become a variable cost considered by the way it is calculated. So that the SMEs are able to include PP 46 2013 as a component of Cost Volume Profit Analysis in making a plan and decision https://doi.org/10.26905/jmdk.v5i2.1803